Faktor-Faktor yang Mempengaruhi Cash Holding Terhadap Perusahaan Manufaktur di Indonesia - Nadia Trisanti; Henny Setyo Lestari (J-MAS (Jurnal Manajemen dan Sains), 2022)
Cash holding is very important in a company, especially in transaction activities and company operations. However, holding excessive cash also has a bad side, namely the loss of the company's opportunity to earn profits because the cash that is only stored will not provide income. The purpose of this study is to obtain empirical evidence whether firm size has a negative effect on cash holding, whether growth opportunities have a positive effect on cash holding, whether cash flow has a positive effect on cash holding, whether cash flow risk has a positive effect on cash holding, whether leverage has a negative effect. on cash holding, whether capital expenditure has a negative effect on cash holding, and dividend payment has a negative effect on cash holding in manufacturing companies in Indonesia. The sampling technique used was purposive sampling and data processing using Eviews 10 and Microsoft Excel 2010. Research during the 2017-2021 period was conducted on 28 companies. The results showed that firm size had a significant effect on cash holding, growth opportunities had a significant effect on cash holding, cash flow had no effect on cash holding, cash flow risk had no effect on cash holding, leverage had a significant effect on cash holding, capital expenditure had no effect on cash. holding, and dividend payments have a significant effect on cash holding.